Strategi Promosi untuk Meningkatkan Jumlah Anggota Koperasi Simpan Pinjam Pembiayaan Syariah Mitra Insan Mandiri - Nurnawati, Rani (LPPM IAIT, 2023)
In the matter of marketing, cooperative institutions will be placed in a market that is likened to a battlefield for many existing savings and loan cooperatives that have been engaged in the same community, it is necessary to create an effective promotional strategy in order to win the competition. Therefore, as the competition between cooperatives and other financial institutions has been emerged, the cooperative management must be able to manage the company effectively, so that consumers or members do not switch to other financial institutions. Apromotional strategy has been commonly practiced by existing financial institutions, henceforward a savings and loan cooperativ must advance its promotional strategy in order to have strong competitiveness by using a good and targeted promotional strategy. A good promotional strategy will place the savings and loan cooperatives in a strong position, especially in the face of current competition. The purpose of this study was to determine the Promotion Strategy and efforts that has been done by KSPPS MIM to increase the number of its members. Data were collected from primary sources through observation and direct interviews with the institutions, and fromsecondary data such as literature, reports, and documents related to the development of cooperative members. The results show that the particular cooperative has implemented promotional strategy through Personal Selling, activation and data collection of members and advertising through digital platform such as social media. The implementation of cooperative education activities is the main focus of the cooperative as an effort to retain and recruit its members.